A Novel Anthraquinone Glycoside From Impatiens balsamina Linn. Seeds - Yadava, R.N.; Jain, Basanti (Asian Journal of Chemistry, 2010)
The present paper describes the isolation and identification of a novel anthraquinone glycoside 1,3,dimethoxy-6, methyl anthraquinone- 8-O-β-D-glucopyranosyl (1 → 4)-O-α-L-rhamnopyranoside.